Effect of sleep quality on weaning from mechanical ventilation: A scoping review - Locihová, Hana; Jarošová, Darja; Šrámková, Karolína; Slonková, Jana; Zoubková, Renáta; Maternová, Klára; Šonka, Karel (The journal of critical care medicine, 2025)
INTRODUCTION: Mechanically ventilated patients have disturbed sleep. AIM OF THE STUDY: To explore whether there is a relationship between successful or unsuccessful weaning of patients and their sleep quality and circadian rhythm. MATERIALS AND METHODS: A scoping review. The search process involved four online databases: CINAHL, MEDLINE, ProQuest, and ScienceDirect. Original studies published between January 2020 and October 2022 were included in the review. RESULTS: Six studies met the inclusion criteria. These studies showed that patients with difficult weaning were more likely to have atypical sleep, shorter REM sleep, and reduced melatonin metabolite excretion. Muscle weakness was an independent factor associated with prolonged weaning from mechanical ventilation and was significantly more frequent in patients with atypical sleep. Heterogeneous patient samples and the methodology of the studies hamper a clear interpretation of the results. CONCLUSIONS: A relationship was found between abnormal sleep patterns, reduced melatonin metabolite (6-sulfa-toxymelatonin) excretion, and unsuccessful weaning. However, the causality is not clear from the existing research.